The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1177/1089253220960255
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Serotonin Syndrome Following Methylene Blue Administration for Vasoplegia After Cardiac Surgery: A Case Report and Review of the Literature

Abstract: Serotonin syndrome is a potentially life-threatening condition associated with increased serotonergic activity in the central nervous system. The increasing incidence of this condition is thought to parallel the increasing use of serotonergic agents in medical practice. The selective serotonin reuptake inhibitors are perhaps the most commonly implicated group of medications associated with serotonin syndrome. This case report describes the occurrence of postoperative serotonin syndrome in a patient on long-ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…However, there was likely dose accumulation that occurred as three doses of methylene blue were given within a 24‐h period. A similar case report in which a patient was on sertraline 100 mg daily and received methylene blue for vasoplegia after coronary artery bypass graft surgery, showed that SS can occur even with just one dose of methylene blue 13 . By contrast, bupropion has no direct/indirect effect on serotonin, despite prior case reports stating this.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, there was likely dose accumulation that occurred as three doses of methylene blue were given within a 24‐h period. A similar case report in which a patient was on sertraline 100 mg daily and received methylene blue for vasoplegia after coronary artery bypass graft surgery, showed that SS can occur even with just one dose of methylene blue 13 . By contrast, bupropion has no direct/indirect effect on serotonin, despite prior case reports stating this.…”
Section: Discussionmentioning
confidence: 97%
“…A similar case report in which a patient was on sertraline 100 mg daily and received methylene blue for vasoplegia after coronary artery bypass graft surgery, showed that SS can occur even with just one dose of methylene blue. 13 By contrast, bupropion has no direct/indirect effect on serotonin, despite prior case reports stating this. Nonetheless, bupropion use is contraindicated with methylene blue as the combination can lead to hypertension, making autonomic instability that occurs with SS harder to treat.…”
Section: Discussionmentioning
confidence: 99%
“…A recent case series of 2 patients suggests HCB could play a role in the stabilisation of capillary membranes, whereas MB cannot do so. This can explain some synergistic effects of HCB and MB in treatment of vasopressor resistant VS 61 . Furnish et al conducted a retrospective cohort study in which they evaluated the effect of MB compared to HCB in the treatment sepsis, with or without shock, were included and randomly allocated in a 1:1 ratio to receive either a continuous infusion of MB (0.5 mg kg -1 h -1 ) for 6 hours or isotonic saline.…”
Section: Methylene Blue Vs Hydroxocobalaminmentioning
confidence: 93%
“…Although the exact mechanism is still unknown, HCB acts like MB, inhibiting NOS and also directly blocking NO. Some authors claim that HCB also interacts with other endogenous vasodilators like carbon monoxide and innate hydrogen sulphide 9,61 . A recent case series of 2 patients suggests HCB could play a role in the stabilisation of capillary membranes, whereas MB cannot do so.…”
Section: Methylene Blue Vs Hydroxocobalaminmentioning
confidence: 99%
“…Basta et al 33 describe an extreme case of vasoplegia after coronary artery bypass grafting surgery needing therapy with methylene blue. While this is not an infrequent situation faced by clinicians in day-to-day practice, but postoperative serotonin syndrome that followed makes us wonder if we must exercise more caution while using this medication on patients receiving SSRIs (selective serotonin reuptake inhibitors; sertraline in this case).…”
mentioning
confidence: 99%